Understanding Alveolar echinococcosis patients' psychosocial burden and coping strategies: a qualitative interview study - Nikendei, Christoph; Greinacher, Anja; Cranz, Anna; Friederich, Hans-Christoph; Stojković, Marija; Berkunova, Anastasiya (PLoS neglected tropical diseases, 2023)
BACKGROUND: Alveolar echinococcosis (AE) is a serious parasitic zoonotic disease that resembles malignancy with clinically silent infiltrative growth predominantly involving the liver. AE patients show high levels of comorbid psychological burden and fear of disease progression. This study aimed to examine AE patients' perspective on their disease-related psychosocial burden using qualitative methods. METHODS: We conducted N = 12 semi-structured interviews with AE patients focusing on their disease-related psychosocial burden, coping strategies, information seeking behavior, and subjective illness concepts. To this end, AE patients from a previous quantitative cross-sectional study were invited to participate. After verbatim transcription, interviews were analyzed thematically. RESULTS: After analysis, data was grouped into five main themes: A) Perceived disease-related burden, B) Coping with disease-related burden, C) Disease-related impact on their social environment, D) Facing the future with the disease, and E) Disease-related information seeking behavior and subjective illness concepts. All participants perceived AE as a severe disease with inextricably linked biological, psychological, and social effects. Key positive influences reported included the provision of information and access to informal and formal support, including the ability to lead active personal and professional lives for as long as possible. Self-directed, web-based information seeking often led to increased feelings of hopelessness and anxiety. CONCLUSION: Our findings underscore the need to consider psychosocial morbidity in AE patient management. To reduce psychological burden, address disease-related apprehensions, and to prevent stigmatization, health professionals need to provide AE patients with comprehensive disease-related information to improve patient and social awareness.
Veröffentlicht: 4. August 2023
Gesehen am 13.09.2023